SOLVENT FREE, ONE POT SYNTHESIS OF SYMMETRIC XANTHENE DYES AND THEIR ELECTROCHEMICAL STUDY - Shabir, Ghulam; Saeed, Aamer (Journal of the Chilean Chemical Society, 2016)
The present paper reports the synthesis of xanthene dyes derivatives from 4, 4’-oxydiphthalic anhydride and 1, 4, 5, 8-naphthalenetetracarboxylic dianhydride (3a-e and 6a-e) with different substituted phenols via Friedel-Crafts acylation reaction in the presence of an ammonium chloride catalyst. The structures of all newly synthesized derivatives were confirmed by the chromatographic, spectral and microelemental data. Dianhydride derivatives with 3-N’, N’-dimethylaminophenol (3d and 6d) and resorcinol (3e and 6e) have been found to be highly fluorescent. Electrochemical study was done to determine band gap energy, LUMO and HOMO level energy. Band gap and LUMO energy levels were found to be lowest in xanthene derivatives 3c and 6c. Dyes 3d, 3e, 6d and 6e were found useful for differential staining of plant cells.